A quadruped robot obstacle avoidance and personnel following strategy based on ultra-wideband and three-dimensional laser radar. (28th July 2022) - Li, Zhi; Li, Bin; Liang, Qixing; Liu, Weilong; Hou, Landong; Rong, Xuewen
To improve the human–computer interaction ability and environmental adaptability of the quadruped robot, especially the ability of the quadruped robot to follow people and avoid obstacles. In this article, the fusion of ultra-wideband positioning technology and three-dimensional laser radar is applied to a quadruped robot. The core is to scan the surrounding obstacle information through three-dimensional laser radar, locate the position of both the quadruped robot and the target person, complete the obstacle avoidance, and follow the task of the quadruped robot through an efficient path planning algorithm. To meet the high-precision positioning requirements, the ultra-wideband positioning system is used in this article. When calculating the coordinates, we propose a three-sided weighted least squares positioning algorithm. To improve the efficiency and stability of the quadruped robot in path search, based on the A* algorithm, this article improves and proposes an incremental A* algorithm based on a sliding window. The feasibility and effectiveness of our method are verified by computer simulation analysis and real experiments of the quadruped robot.